2017
DOI: 10.1021/acsami.7b00150
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Glass-Like Behavior and Topological Hall Effect in SrRuO3/SrIrO3 Superlattices for Oxide Spintronics Applications

Abstract: The heterostructure interface provides a powerful platform for exploring rich emergent phenomena, such as interfacial superconductivity and nontrivial topological surface states. Here, SrRuO/SrIrO superlattices were epitaxially synthesized. The magnetic and magneto-transport properties of these superlattices were characterized. A broad cusp-type splitting in the zero-field-cooling/field-cooling temperature-dependent magnetization and magnetization relaxation, which follows the modified stretched function model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 35 publications
9
49
0
Order By: Relevance
“…In particular, both positive and negative THE components can be identified at certain temperatures (e.g., 10 K) In addition, we confirm that the THE is driven by the magnetization reversal process due to the fact that the peak position of THE (H P ) scales nicely with the coercive field (H C ). We note that in previous studies of ultra-thin SrRuO 3 film systems, the THE emerges as the consequence of the enhanced DM interaction, as well as reduced ferromagnetism due to the interface effect 11,16,17 . Similarly, in our system, the ILG induced large proton compositional gradient at the boundary of the ferromagnetic to paramagnetic phase transition would lead to an enhanced DM interaction as well as reduced ferromagnetism, and both favor the emergence of THE.…”
Section: Reversible Control Of Magnetism Through Proton Evolutionmentioning
confidence: 59%
See 1 more Smart Citation
“…In particular, both positive and negative THE components can be identified at certain temperatures (e.g., 10 K) In addition, we confirm that the THE is driven by the magnetization reversal process due to the fact that the peak position of THE (H P ) scales nicely with the coercive field (H C ). We note that in previous studies of ultra-thin SrRuO 3 film systems, the THE emerges as the consequence of the enhanced DM interaction, as well as reduced ferromagnetism due to the interface effect 11,16,17 . Similarly, in our system, the ILG induced large proton compositional gradient at the boundary of the ferromagnetic to paramagnetic phase transition would lead to an enhanced DM interaction as well as reduced ferromagnetism, and both favor the emergence of THE.…”
Section: Reversible Control Of Magnetism Through Proton Evolutionmentioning
confidence: 59%
“…Recently, there are also emerging research interests in SrRuO 3 system on its exotic topological spin texture with the reports of the topological Hall effect (THE), which is attributed to the inequivalent interfaces in the studied ultra-thin films 11,13,[16][17][18][19][20] . Furthermore, some recent results demonstrated nicely the electric-field controlled THE in ultrathin SrRuO 3 films through the dielectric and ferroelectric modulations 11,13 , although the resultant effect remains subtle, reminiscent of its electric-field controlled magnetic state.…”
mentioning
confidence: 99%
“…Recently, it has been shown that topologically nontrivial spin textures, such as skyrmions, which are stabilized through Dzyaloshinskii–Moriya (DM) interactions induced by broken spatial inversion symmetry, can give rise to additional contributions to Hall resistivity, known as the topological Hall effect . Given the richness of physics underlying behind the topological Hall effect as well as its potential for device applications, materials and artificial structures that exhibit this Hall effect have been intensively explored …”
Section: Introductionmentioning
confidence: 99%
“…The results have demonstrated that high-quality oxide heterointerfaces provide a platform for designing topological spin structures. This type of experiment has been spreading into more bilayers of other oxide combinations and even superlattices [138].…”
Section: -2 Topological Spin Structures In Oxide Interfacesmentioning
confidence: 99%